Can the Right to A Good and Healthy Environment be Claimed as a Human Right? - Achmad Romsan; Meria Utama; Irsan Irsan; Akhmad Idris; Tuti Indah Sari; Azhar Azhar; Herwin Herwin; Marieska Verawaty; Hamet Hashemi; Maysam Aboutalebi Najafabadi (Sriwijaya Law Review, 2024)
Land fires in South Sumatra are an annual problem during the long dry season. It was recorded that in 2015, 2016, 2017, and 2018, the land fires spread massively in the four districts of South Sumatra. The peatlands located within oil palm plantations in the Districts of Ogan Komering Ilir, Banyuasin, Musi Banyuasin, and the district of Ogan Ilir were the source of the fire. The haze not only attracts national but also international attention. Besides human contribution to land fire, climate change should also be considered. The role of El Nino makes the season uncertain. Land fires affect human health and other human activities in the affected areas. Three legal instruments guarantee and protect the people's right to the environment, i.e., The 1945 Indonesian Constitution, the 2009 Law No. 32 on the Environment, and the 1999 Law No. 39 on Human Rights. The problem raised herein is to what extent people can claim the right to a clean environment as human rights guaranteed and protected in those legal instruments. The results of the discussion show that those three legal instruments do not protect people whose human rights have been violated. This is because 2000 Law No. 26 on Human Rights has no jurisdiction over environmental matters. It is suggested that establishing a special Environmental Court is the solution to protect community environmental human rights cases.